Green synthesis of zinc oxide nanoparticles using lychee peel and its application in anti-bacterial properties and CR dye removal from wastewater. (June 2023) - Sachin,; Jaishree,; Singh, Nahar; Singh, Rajni; Shah, Kalpit; Pramanik, Biplob Kumar
Abstract: In nanoscience and nanobiotechnology, using plant extracts in synthesizing metal nanoparticles (NPs) has recently come to light as an exciting opportunity with several benefits over traditional physicochemical methods. In the present work, zinc oxide (ZnO) based nanoparticles (NPs) were synthesized by green chemistry route using lychee peel extract to capture hazardous congo red dye from wastewater and illustrate their antimicrobial behavior. The X-Ray Diffraction (XRD) spectra confirm the wurtzite crystal structure, and Fourier Transform Infrared (FTIR) spectra confirm the functional group in ZnO, which is suitable for dye adsorption. It was found that the NPs were spherical and had a size of <10 nm. The synthesized ZnO NPs could effectively remove >98% of CR dye from wastewater within 120 min of contact time at a wide pH range from 2 to 10. The primary mechanism involved in removing dye was the electrostatic interaction between ZnO adsorbent and CR dye. The antimicrobial performance of synthesized ZnO NPs was found to show 34% inhibition against Bacillus subtilis (ATCC 6538), 52% against Escherichia coli (ATCC 11103), 58% against Pseudomonas aeruginosa (ATCC 25668) and 32% against Staphylococcus aureus (ATCC 25923) using well diffusion assay. ZnO demonstrates a suitable anti-bacterial property over both gram-positive and gram-negative pathogenic bacteria. Overall, the green synthesized method for developing ZnO NPs shows promising and significant anti-bacterial performance and is a highly potential adsorbent for removing CR dye from wastewater. Graphical abstract: Image 1 Highlights: Zinc oxide nanoparticles (ZnO NPs) are synthesized by an eco-friendly green process. Synthesized ZnO NPs remove congo red (CR) dye in wide pH range from 2 to 10. Synthesized ZnO NPs shows removal efficiency of >98% for CR dye. Chemisorption was the major mechanism for CR dye removal. ZnO NPs show good anti-microbial performance for gram-positive and gram-negative bacteria.